Freire (with Bakhtin) and the Dialogic Classroom Seminar - Bowers, Rick (Alberta Journal of Educational Research, 2005)
This article on pedagogy in the classroom seminar combines the basic principles of dialogue and liberation as expressed especially by 20th-century thinkers Bakhtin and Freire. It argues for a pedagogy of educational growth and facilitation of ideas. Through learner-centered knowledge, dialogic interaction, open exploration, mutual respect, and problem-based learning—as opposed to a pedagogy of conflict, including scenarios of confrontation, monologic assertions of instruction, and expert communiqués—the classroom seminar undergoes authentic liberation and discovery. At all points the classroom must be free from coercion and open to alternative perspectives in order to weigh evidence and arguments as objectively as possible, to break patterns of vertical authority, and to involve all participants in their own education. Not usually compared, these Bakhtinian and Freirean procedures provide sustainable, compassionate, and empowering possibilities for the university classroom seminar in North America and elsewhere.